2014
DOI: 10.1128/jb.02090-14
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Essentiality of Glutamate Racemase in Mycobacterium smegmatis

Abstract: The mycobacterial cell wall frequently has been used as a target for drug development, and D-glutamate, synthesized by glutamate racemase (MurI), is an important component of peptidoglycan. While the essentiality of the murI gene has been shown in several bacterial species, including Escherichia coli, Bacillus anthracis, and Streptococcus pneumoniae, studies in mycobacteria have not yet provided definitive results. This study aimed to determine whether murI is indeed essential and can serve as a possible targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…29, 30 The murl mutant of E. coli lysed in the absence of D-glutamic acid, 31 and the murl mutant of M ycobaterium smegmatis also showed aberrant cell shapes. 32 Although the precise mechanisms remain unknown, the deletion of alr not only led to growth arrest but also to cell death, indicating that alr might be a potential bactericidal target for the inhibition of S. mutans .…”
Section: Discussionmentioning
confidence: 99%
“…29, 30 The murl mutant of E. coli lysed in the absence of D-glutamic acid, 31 and the murl mutant of M ycobaterium smegmatis also showed aberrant cell shapes. 32 Although the precise mechanisms remain unknown, the deletion of alr not only led to growth arrest but also to cell death, indicating that alr might be a potential bactericidal target for the inhibition of S. mutans .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our group demonstrated that glutamate racemase deletion mutants of M. smegmatis mc 2 155 were unable to grow in the absence of D-glutamate (Li et al, 2014). To investigate this further, we set up growth experiments in which the incubation period was extended to > 100 h, both in the absence and presence of D-glutamate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The murI gene has been reported as essential in E. coli (Doublet et al ., ), Bacillus anthracis (Oh et al ., ), B. subtilis (Kimura et al ., ), Helicobacter pylori (Lundqvist et al ., ) and Streptococcus pneumoniae (de Dios et al ., ), among others. Recent work has confirmed its essentiality in both M. smegmatis (Li et al ., ) and M. tuberculosis (Morayya et al ., ; Griffin et al ., ), contradicting earlier studies (Sassetti et al ., ; Harth et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations